Elevated levels of D-dimer in patients with COVID-19: prognosis value - Oualim, Sara (Pan Afr Med J, 2020)
INTRODUCTION: coronavirus disease is now a global pandemic due to rapid human-to-human transmission. It can cause mild to fatal respiratory, cardiovascular, and neurological diseases. We aimed to find out whether elevated D-dimer levels are a predictor of the bad progression of COVID-19 to help reducing the mortality. METHODS: the data of COVID-19 patients from March 21, 2020 to April 24, 2020 were retrieved from the Cheick Khalifa Hospital database. We used the receiver operating characteristic (ROC) curve to get the optimum cutoff value of D-dimer levels on admission and after 5 days. We used these cutoffs to divide patients into two groups and compare the in-hospital mortality between them to assess the prognosis value of D-dimer levels. RESULTS: the data of COVID-19 patients from March 21, 2020 to April 24, 2020 were retrieved from the Cheick Khalifa Hospital database. We used the receiver operating characteristic (ROC) curve to get the optimum cutoff value of D-dimer levels on admission and after 5 days. We used these cutoffs to divide patients into two groups and compare the in-hospital mortality between them to assess the prognosis value of D-dimer levels. 89 patients were included in this study, of whom 79 were discharged and 10 died in hospital. The optimum cutoff value to predict mortality in patient using D-dimer levels on admission was 668 ng/ml (sensitivity 90%, specificity 63.3%, Areas under the ROC curve 0,775). As for D-dimer levels on day 5, it was 1360 ng/ml (sensitivity 100%, specificity 88,6%, Areas under the ROC curve 0.946). The group with D-dimer levels on day 5 > 1360 ng/ml (19 patients) had a worst evolution and a higher incidence of mortality compared to the group with D-dimer < 1360 ng/ml (69 patients) (10/19 vs 0/69, P = 0,0002). CONCLUSION: D-dimer greater than 1360 ng/ml on day 5 could help clinicians identify patients with poor prognosis at an early stage of COVID-19.